ASIATIDRI: POTENSI KOMBINASI DAUN ARA SUNGSANG (ASYSTASIA GANGETICA SSP. MICRANTHA) DAN SELEDRI (APIUM GRAVEOLENS L.) SEBAGAI ALTERNATIF TEH HERBAL ANTI DIABETES MELLITUS - Putri, Ayu Nirarai; Sari, Aulia Murti Novita; Eldy, Wikke Febrya (Program Kreativitas Mahasiswa - Penelitian, 2013)
Study on the potential combination of Asystasia gangetica ssp. micrantha and Apium graveolens L. Â tea for anti diabetes mellitus and its effective dose has been conducted on male Mus musculus. Complete random design with 5 treatments: positive and negative controls, 31,43 mg/30 g body weight (bw), 54.60 mg/30 g bw, 62.86 g/30 g bw with 4 replications was applied. Data was analyzed using ANOVA and LSD at 5%. After seven days infusion treatments indicated that there was significantly decrease in blood glucose level. The highest dose of 62.86 mg/30 g Â Â decreased miceâs blood glucose level closed to their normal level.Keywords: Asiatidri, diabetes mellitus, blood glucose level.